Submission Guidelines - College of Education, The Chairperson Committee on Publications (Philippine Journal of Education Studies (formerly the Education Quarterly), 2010)
The Education Quarterly is the refereed journal of the College of Education, University of the Philippines, Diliman. Graduates, students, and scholars from any reputable educational/academic institution are welcome to submit their manuscripts for evaluation.